2022
DOI: 10.3389/fimmu.2022.952639
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent Chromium Exposure Induces Intestinal Barrier Damage via Activation of the NF-κB Signaling Pathway and NLRP3 Inflammasome in Ducks

Abstract: Hexavalent chromium [Cr(VI)] is a dangerous heavy metal which can impair the gastrointestinal system in various species; however, the processes behind Cr(VI)-induced intestinal barrier damage are unknown. Forty-eight healthy 1-day-old ducks were stochastically assigned to four groups and fed a basal ration containing various Cr(VI) dosages for 49 days. Results of the study suggested that Cr(VI) exposure could significantly increase the content of Cr(VI) in the jejunum, increase the level of diamine oxidase (DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that Cr(VI) exposure increases H 2 O 2 and MDA levels while decreasing T-SOD and CAT activities, leading to oxidative stress [34,[36][37][38][39][40][41]. Xing et al reported that exposure to Cr(VI) resulted in an increase in H 2 O 2 and MDA levels, as well as a decrease in T-SOD and CAT activities, leading to oxidative stress in the intestinal barriers of ducks [42] Similarly, Cr(VI) has been shown to lower SOD and GSH levels while elevating MDA levels in the kidney tissue of broilers [43]. Consistent with prior studies, our findings indicate that sustained exposure to Cr(VI) attenuates the defense system against free radicals, characterized by a decline in T-SOD, SOD, GSH-Px, GSH, and CAT activities, coupled with elevated MDA and H 2 O 2 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that Cr(VI) exposure increases H 2 O 2 and MDA levels while decreasing T-SOD and CAT activities, leading to oxidative stress [34,[36][37][38][39][40][41]. Xing et al reported that exposure to Cr(VI) resulted in an increase in H 2 O 2 and MDA levels, as well as a decrease in T-SOD and CAT activities, leading to oxidative stress in the intestinal barriers of ducks [42] Similarly, Cr(VI) has been shown to lower SOD and GSH levels while elevating MDA levels in the kidney tissue of broilers [43]. Consistent with prior studies, our findings indicate that sustained exposure to Cr(VI) attenuates the defense system against free radicals, characterized by a decline in T-SOD, SOD, GSH-Px, GSH, and CAT activities, coupled with elevated MDA and H 2 O 2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The final dietary contents of Cr(VI) in the 4 groups were as follows: 0 (control), low dose of K 2 Cr 2 O 7 (9.28 mg/kg LCr), medium dose of K 2 Cr 2 O 7 (46.4 mg/kg MCr), and high dose of K 2 Cr 2 O 7 (232 mg/kg HCr) respectively. The dosage of hexavalent chromium was referenced to previous experimental results [42]. The source of Cr(VI) was 99.8% pure potassium dichromate (K 2 Cr 2 O 7 ) of analytical grade from Heng da Chemical of Tianjin, China.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Inflammasomes are intracellular aggregated protein complexes acting as sensors and effectors of innate immunity, capable of responding to various stimuli including oxidants . For example, in a study involving oral chromate-induced intestinal barrier damage, the formation of inflammasomes was observed . Further investigations through in vitro and animal studies on chromate-induced allergies revealed that the accumulation of reactive oxygen species (ROS) caused by Cr­(VI) led to potassium efflux, subsequently activating inflammasomes. , Inflammasomes may influence immune responses, promote chronic inflammation, and exacerbate the genetic toxicity of Cr­(VI).…”
Section: Introductionmentioning
confidence: 99%